Irregular satellites of Jupiter: Three-dimensional study of binary-asteroid captures - Gaspar, H. S. [UNESP]; Winter, O. C. [UNESP]; Neto, Vieira [UNESP] (Oxford University Press (OUP), 2013)
Among the hidden pieces of the giant puzzle, which is our Solar system, the origins of irregularsatellites of the giant planets stand to be explained, while the origins of regular satellites arewell explained by the in situ formation model through matter accretion. Once they are notlocally formed, the most acceptable theory predicts that they had been formed elsewhere andbecame captured later, most likely during the last stage of planet formation. However, underthe restricted three-body problem theory, captures are temporary and there is still no assistedcapture mechanism which is well established. In a previous work, we showed that the capturemechanism of a binary asteroid under the co-planar four-body scenario yielded permanentcaptured objects with an orbital shape which is very similar to those of the actual progradeirregular Jovian satellites. By extending our previous study to a 3D case, here we demonstratethat the capture mechanism of a binary asteroid can produce permanent captures of objects byitself which have very similar orbits to irregular Jovian satellites. Some of the captured objectswithout aid of gas drag or other mechanisms present a triplet: semi-major axis, eccentricityand inclination, which is comparable to the already known irregular Jovian objects. © 2013 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Formation; Planets and satellites